Architecting solutions with SAP business technology platform : an architectural guide to integrating and extending enterprise solutions using SAP BTP /: an architectural guide to integrating and extending enterprise solutions using SAP BTP. (2022) - Simsekler, Serdar; Du, Eric
No abstract available